SEASONAL VARIATION AND ASSESSMENT OF HEAVY METALSPOLLUTION IN SEDIMENTS FROM SELECTED STATIONS INTIGRIS AND EUPHRATES RIVERS, CENTRAL IRAQ - Rabee, Adel; Abd own, Abd-Al-Husain; Al-Fatlawy, Yaaroub; Abd own, Abd-Al-Husain (Iraqi Journal of Science, 2024)
In this study, four sampling stations were selected from two locates on theTigris river (Baghdad region) and others on the Euphrates river (Al-AnbarGovernorate) in order to determine concentrations, seasonal variation and pollutionintensity assessment of heavy metals (Ni, Cu, Pb, Mn and Cd) in the two riverssediments. Distribution of studied metals showed that stations in the Tigris rivergenerally had higher concentrations than stations in Euphrates river. Manganese wasfound at high concentrations in all studied stations and ranged between 200 - 500ppm, while Cd was found at the lowest concentrations and ranged between notdetected to 1.8 ppm during study period. Based on index of geoaccumulation(I-geo) for studied heavy metals indicates that the surface sediments in the studiedstations are unpolluted by Ni and Mn, while unpolluted to slightly polluted by Pband Cd except the Cd at south of Baghdad station (moderately polluted). The I-geofor Cu indicate the sediments were unpolluted to slightly polluted in the Tigrisstations, and unpolluted in the Euphrates stations. The calculated enrichment factor(EF) indicate that all stations can be classified as minimal enrichment for Ni,moderate enrichment for Cu and significant enrichment for the elements Pb and Cd.